Altering allergenicity of cow's milk by food processing for applications in infant formula. Issue 1 (2nd January 2019) - Golkar, Abdolkhalegh; Milani, Jafar M.; Vasiljevic, Todor
ABSTRACT: Cow's milk-based infant formulas have a long tradition in infant nutrition, although some infants are unable to use them due to presence of several known allergens. Various processing methods have been identified capable of reducing cow's milk protein allergenicity including thermal and non-thermal methods and their combinations. Heat treatment and enzymatic hydrolysis have been in production of hypoallergenic infant formulas. However, modulation of allergenic epitopes depends on the extent of heat treatment applied, which consequently may also reduce a nutritional value of these proteins. In addition, enzymatic hydrolysis may not target allergenic epitopes thus allergenicity may persist; however released peptides may have detrimental impact on taste and functional properties of final products. Modulation of allergenicity of milk proteins appears to require a concerted effort to minimize detrimental effects as clinical studies conducted on commercial hypoallergenic formulas demonstrated persistence of allergic symptoms. This article covers traditional and novel processing methods and their impact on reduction of cow's milk allergenicity in milk-based infant formulas.